2012
DOI: 10.1103/physreva.86.013422
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of pair creation due to a steady magnetic field

Abstract: We investigate the electron-positron pair creation process in a supercritical static electric field in the presence of a static magnetic field that is perpendicular. If both fields vary spatially in one direction the dynamics can be reduced to a set of one-dimensional systems. Using a generalized computational quantum field theoretical procedure, we calculate the time dependence of the spatial density for the created electrons. In the presence of the magnetic field, a significant amount of suppression of pair … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 56 publications
(58 reference statements)
0
27
1
Order By: Relevance
“…However, a recent work [13] has introduced a computational algorithm that permits us to study the decay process of the vacuum for the case where the magnetic field is perpendicular to the electric field and both fields have arbitrary spatial extensions along this polarization direction. It was shown that the three dimensional dynamics can be reduced to a quasi one-dimensional set of equations.…”
Section: /8/2012mentioning
confidence: 99%
“…However, a recent work [13] has introduced a computational algorithm that permits us to study the decay process of the vacuum for the case where the magnetic field is perpendicular to the electric field and both fields have arbitrary spatial extensions along this polarization direction. It was shown that the three dimensional dynamics can be reduced to a quasi one-dimensional set of equations.…”
Section: /8/2012mentioning
confidence: 99%
“…(14)(15)(16)(17)(18). Figure 1 shows the fields |ReE|, |ReH|, and invariants ǫ, and η as a function of ξ for µ = −1 at z = 0 the electric and magnetic fields are parallel to each other.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that QED effects can be experimentally studied with soon-coming laser facilities like Extreme Light Infrastructure (ELI) and High Power laser Energy Research (HiPER) [16]. Su et al in [17] have investigated the particle creation process in the presence of magnetic field perpendicular to the electric field. It has also been shown [18] that the magnetic field can diminish the pair production.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that a spatially modulated electric field inhibits the pair production [6]. Also, for constant magnetic fields perpendicular to the electric field, it was found the pair production decreases [30]. These questions deserve further investigations in the future.…”
mentioning
confidence: 93%